2020
DOI: 10.3390/world1030022
|View full text |Cite
|
Sign up to set email alerts
|

Early Lessons of COVID-19 for Governance of the North American Great Lakes and the Baltic Sea

Abstract: The commitment to advance the protection of the North American Great Lakes and the Baltic Sea continues during the COVID-19 pandemic. The resilience of the research community was displayed as policy decisions were made for the first virtual conferences this year to share scientific findings and expertise in both regions. As this pandemic continues to challenge the world, countries have responded to the threat and continue to deal with the uncertainties of this wicked transboundary problem in many different way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This large population is affected by and affects the Sea through activities such as fishing, agriculture, shipping, boating, land use modifications, and polluting. The consequences of these activities are wicked problems such as eutrophication and climate change; problems that are complex and subject to conflicting stakeholder values and perceptions on the root causes of the problem, and hence the solutions [2]. A collaboration of leading scientists found that the Baltic Sea is the world's fastest warming marine system and as such, can serve as a time machine to study future coastal perturbations [3].…”
Section: Introductionmentioning
confidence: 99%
“…This large population is affected by and affects the Sea through activities such as fishing, agriculture, shipping, boating, land use modifications, and polluting. The consequences of these activities are wicked problems such as eutrophication and climate change; problems that are complex and subject to conflicting stakeholder values and perceptions on the root causes of the problem, and hence the solutions [2]. A collaboration of leading scientists found that the Baltic Sea is the world's fastest warming marine system and as such, can serve as a time machine to study future coastal perturbations [3].…”
Section: Introductionmentioning
confidence: 99%